2022
DOI: 10.1017/s2045796021000846
|View full text |Cite
|
Sign up to set email alerts
|

A response to yet another defence of ECT in the absence of robust efficacy and safety evidence

Abstract: It is estimated that electroconvulsive therapy is still administered to approximately a million people a year. It involves passing enough electric current through the human brain, eight to twelve times, to cause convulsions, in the hope of somehow alleviating emotional suffering, primarily depression. There have only ever been 11 placebo-controlled studies (where general anaesthesia is administered but the electric shock is withheld), all of which were pre-1986, had very small sample sizes and were seriously m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…There are six standard responses used to try to counteract the absence of any robust evidence that ECT is better than placebo (Read, 2022) (see Table 2).…”
Section: The Six Defences Against Having No Robust Evidencementioning
confidence: 99%
“…There are six standard responses used to try to counteract the absence of any robust evidence that ECT is better than placebo (Read, 2022) (see Table 2).…”
Section: The Six Defences Against Having No Robust Evidencementioning
confidence: 99%
“…Our audit had revealed that after nearly 20 years of ECTAS' efforts to 'improve the quality of care', only 24% of ECT clinics reported using any standardised tool at all, and 44% of those that did were, inappropriately, using the MMSE. This is a serious safety matter Read (2022). Persistent or permanent memory loss is reported by Sackeim et al (2007) and Rose et al (2003) between 12% and 55%, respectively, with particularly high rates in women and older people.…”
Section: Assessing Cognitive Damagementioning
confidence: 99%
“…Most of the arguments of Meechan et al were addressed in a paper (Read, 2022) identifying the many ‘errors, misrepresentations, omissions, inconsistencies and logical flaws’ in their previous attempt to dismiss these inconvenient truths, and to discredit the evidence that ECT causes memory loss, brain damage, cardiovascular events and, rarely, death. We have space here for only a few.…”
Section: Electroconvulsive Therapymentioning
confidence: 99%
“…Meechan et al's concerns about suicide studies and patient expectancy have been addressed elsewhere (Read, 2022; Read & Moncrieff, 2022; Read et al, 2019).…”
Section: Electroconvulsive Therapymentioning
confidence: 99%